The Developmental and Educational Impact of Hearing Impairment in Aboriginal Children Living in Remote Australia – A Data Linkage Study - Md Shajedur Rahman Shawon (International Journal of Population Data Science, 2020)
Introduction High prevalence of otitis media (OM) and hearing impairment (HI) in Aboriginal children in Australia’s Northern Territory (NT) is well documented. HI may be associated with poorer outcomes in early childhood development, school attendance and academic achievement. However, these associations have not been investigated in this population.